Rituals of the past: prehispanic and colonial case studies in Andean archaeology - Rosenfeld, Silvana A., editor; Bautista, Stefanie L., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2017)
Through the study of archaeological, ethnographic, linguistic, and historical evidence from northern Peru to northern Chile, Bolivia, and northwest Argentina, the authors in this volume show the significance of ritual from pre-contact to present day in the Andes. These volume essays deal with theoretical and methodological concerns in anthropology and archaeology including non-human and human agency, the development and maintenance of political and religious authority, ideology, cosmologies, and social memory, and their relationships with ritual action. By providing a diachronic and widely regional perspective on ritual in the Andes, this volume shows how ritual is both persistent and dynamic and is key in understanding many aspects of the formation, reproduction, and change of life in past Andean societies.
An archaeology of rituals / Silvana A. Rosenfeld and Stefanie L. Bautista -- The nature of ritual space at Chavín de Huantar / John Rick -- Not just a pyramid scheme: diversity in ritual architecture at Chavín de Huantar / Daniel Contreras -- From ritual to ideology: ritual activity and artistic representations in the northern highlands of Peru in the formative period / Yoshio Onuki -- Architecture and ritual practices at Huaca A of Pampa de las Llamas- Moxeke / Rafael Vega-Centeno -- Territoriality, monumentality, and religion in formative period Nepeña, coastal Áncash / David Chicoine, Hugo Ikebara, and Koichiro Shibata, and Matthew Helmer -- Ritual practice at the end of empire: evidence of an abandonment ceremony from Pataraya, a Wari outpost on the south coast of Peru / -- Matthew Edwards -- From the domestic to the formal: a view of daily and ceremonial practices from Cerro de Oro during the early middle horizon / Francesca Fernandini and Rafael Ruales -- The demise of the ruling elites: terminal rituals in the pyramid complexes of Panquilma, Peruvian central coast / Camila Capriata Estrada and Enrique Lopez-Hurtado -- Reconstructing early colonial Andean ritual practice at Pucará, Peru: an architectural approach / Sarah Abraham -- Ritual as inter-action with non-humans: pre-Hispanic mountain pass shrines in the southern Andes / Axel Nielsen, Carlos Angiorama, and Florencia Avila -- Mining, ritual, and social memory: an exploration of toponymy in the Ica Valley, Peru / Hendrik van Gijseghem and Verity Whalen -- Rituals of the past: final comments / Jerry D. Moore.
Keywords: Indians of South America -- Andes Region -- Rites and ceremonies; Indians of South America -- Peru -- Rites and ceremonies; Excavations (Archaeology) -- Andes Region; Excavations (Archaeology) -- Peru; Andes Region -- Antiquities; Peru -- Antiquities